Boundary Crossing and Boundary Objects - Akkerman, Sanne F.; Bakker, Arthur (Review of educational research, 2011)
Diversity and mobility in education and work present a paramount challenge that needs better conceptualization in educational theory. This challenge has been addressed by educational scholars with the notion of boundaries, particularly by the concepts of boundary crossing and boundary objects. Although studies on boundary crossing and boundary objects emphasize that boundaries carry learning potential, it is not explicated in what way they do so. By reviewing this literature, this article offers an understanding of boundaries as dialogical phenomena. The review of the literature reveals four potential learning mechanisms that can take place at boundaries: identification, coordination, reflection, and transformation. These mechanisms show various ways in which sociocultural differences and resulting discontinuities in action and interaction can come to function as resources for development of intersecting identities and practices.